Spark Publishing and Printing House : short-run managerial decision raises a Hamlet-like dilemma (SPPH) - Dave, Shruti, (SAGE Knowledge. Cases., 2017)
Spark Publishing and Printing House is a comprehensive case on relevant costs analysis for short run alternative choice decisions. It stresses the importance of future differential cash flow analysis and highlights the irrelevance of past and non differential costs for managerial decisions. SPPH is a reputed publishing and printing house. It has two departments: Publishing and Printing and Distribution. SPPH has received a proposal from Fine Printing Press to take up its printing and distribution work for initial period of one year. The managerial decision involved is whether to outsource or to maintain status quo. Relevant cost analysis is to be used to determine which alternative is cost effective.